Quercetin improve ischemia/reperfusion‐induced cardiomyocyte apoptosis in vitro and in vivo study via SIRT1/PGC‐1α signaling. Issue 6 (17th January 2019) - Tang, Jiayou; Lu, Linhe; Liu, Yang; Ma, Jipeng; Yang, Lifang; Li, Lanlan; Guo, Hong; Yu, Shiqiang; Ren, Jun; Bai, Heping; Yang, Jian
Abstract: Aim: To evaluate the effects of quercetin to improve ischemia/reperfusion‐induced cardiomyocyte apoptosis in vitro and in vivo study. Methods: The cells were divided into five groups: model control (MC) group was ischemia/reperfusion (I/R) model group; DL group was treated with 25 mL/L quercetin based on MC group; DM group was treated with 50 ml/L quercetin based on MC group; DH group was treated with 100 mL/L quercetin based on MC group; Meto group was treated with metoprolol based on MC group. In the in vivo study, the rats were divided into five groups: MC group was I/R model group; DL group was treated with 25 mg/kg quercetin; DM group was treated with 50 mg/kg quercetin; DM group was treated with 100 mg/kg quercetin; Meto group was treated with Meto as positive drug. Results: The cell apoptosis rates of quercetin treated groups (DL, DM, and DH groups) were significantly suppressed compared with the MC group. The silent information regulatory factor 1 (SIRT1), peroxisome proliferators‐activated receptor‐γ coactivator‐1α (PGC‐1α), and Bcl‐2 proteins expression of quercetin treated were significantly upregulation compared with MC group ( P  < 0.05, respectively), and Bax protein expression of quercetin treated group was significantly downregulation compared with MC group ( P  < 0.05, respectively). In the vivo study, the myocardial pathological morphology of quercetin treated groups was improved. The cell apoptosis number of quercetin treated group were significantly suppressed compared with MC group by terminal deoxynucleotidyl transferase dUTP nick end labeling assay ( P  < 0.05, respectively). SIRT1, PGC‐1a, Bcl‐2, and Bax proteins expressions of quercetin treated groups were significant differences compared with MC group in myocardial tissue ( P  < 0.05, respectively). Conclusion: Quercetin had improved the myocardial ischemia/reperfusion‐induced cardiomyocyte apoptosis via SIRT1/PGC‐1α signaling. Abstract : In conclusion, quercetin might have improved the myocardial ischemia/reperfusion (MI/R) induced cardiomyocyte apoptosis via silent information regulatory factor 1/peroxisome proliferators‐activated receptor‐γ coactivator‐1α (SIRT1/PGC‐1α) signaling pathway with dose‐dependent.